Numerical Experiments to Obtain the Scaling Laws for Neutron Yield on Mather-Type Plasma Focus Machines Below 500 Joules - Singh, A.; Lee, S.; Saw, S.H. (Kathmandu University Journal of Science Engineering and Technology, 2014)
In this paper, we explain how we have fitted Lee‘s 5-phase and 6-phase model code to analyze the current waveforms of 6 small plasma focus machines (below 500 Joules) working in deuterium gas medium. Using the information from the code fitted to these current waveforms, the scaling laws for these small-energy machines were obtained as follows: